Komparasi Fee Based Income pada Bank Konvensional dan Bank Syariah di Indonesia (Studi Laporan Keuangan) - Fitria Ayu Lestari Niu; Youlanda Hasan (Tasharruf: Journal Economics and Business of Islam, 2019)
Fee-based income which is another operating income is proportional to the banking operational income. The elements of operating income included in the group fee based income are commission and provision income, income from foreign exchange or foreign exchange transactions and other operating income. This study aims to describe the comparison of the acquisition of fee-based income in conventional banks and Islamic banks by using secondary data in the form of financial reports in 2014-2015 which were analyzed for comparison using ananalysis intercompany basis through a descriptive quantitative approach. The results showed that the comparison of fee-based income in the conventional bank group was surpassed by Bank Mandiri, which was able to achieve the highest fee-based income compared to BRI and BNI in the 2014-2018 period. Whereas the sharia bank group was outperformed by Bank Syariah Mandiri with the highest fee-based income compared to BRIS and BNIS in the 2014-2018 period. The acquisition of fee-based income in the conventional bank group compared to Islamic banks was outperformed by Conventional Banks namely Bank Mandiri, which each year significantly won the fee-based income highest. Whereas in the proportion of fee-based income to operating income at conventional banks, Bank Mandiri was still in the first position with the highest proportion of 28.61%, followed by BNI in the second position and BRI in the third position. As for Islamic banks, the average proportion of fee-based income to operating income was also occupied by Bank Syariah Mandiri with a gain of 12.89%, followed by BRIS in the second position with 4.84% and the last BNIS of 3.71%.